Choline chloride-based deep eutectic solvents as green extractants for the isolation of phenolic compounds from biomass. (1st August 2021) - Alam, Md. Asraful; Muhammad, Gul; Khan, M. Nuruzzaman; Mofijur, M.; Lv, Yongkun; Xiong, Wenlong; Xu, Jingliang
Abstract: Bioresource valorization to obtain valuable phenolic compounds for medicinal, nutraceutical, food, and cosmetic applications are critical for a current and future sustainable and bio-based economy. Renewable, environmentally friendly, and non-toxic choline chloride-based deep eutectic solvents are the newest and utmost environmentally friendly alternatives to conventional organic solvents for the pretreatment and extraction of phenolic compounds. Recently, numerous studies have focused on phenolic compound extraction using choline chloride-based deep eutectic solvents as solvents or catalysts. Process variable optimization has been reported in terms of kinetic modeling and mechanisms involved in phenolic compounds extraction. This paper describes the cutting-edge methods used to extract phenolic compounds from different bio-based sources using choline chloride-based deep eutectic solvents. In addition, the factors affecting, kinetic models, and mechanisms involved in phenolic compound extraction using choline chloride-based deep eutectic solvents are thoroughly summarized. Moreover, future predictions, challenges, and anticipated growth in this field are addressed and can be used for biomass valorization. Highlights: Extraction of phenolic compounds using deep eutectic solvents is promising. Extraction mechanism depends on the nature of the deep eutectic solvent components. Scaling up should be optimized using experimental and computational approaches. Recovery of phenolic compound from solvent is difficult due to low vapor pressure.